2011
DOI: 10.1002/jctb.2700
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous nitrification and denitrification with electricity generation in dual‐cathode microbial fuel cells

Abstract: BACKGROUND: Nitrogen removal using microbial fuel cells (MFCs) is of great interest owing to the potential benefits of bioenergy production. In this study, simultaneous nitrification and denitrification in dual-cathode MFCs was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 22 publications
(32 reference statements)
1
36
2
Order By: Relevance
“…The low TN removal efficiency observed in this study could be due to several factors: 1) the rotation of the cathode discs which exposes the biofilm to oxygen, thus increasing COD losses due to aerobic oxidation; 2) in this study, oxidation of organic matter, nitrification and denitrification occurred in the same reactor, thus increasing competition between denitrifiers and aerobic heterotrophs for COD; whereas in previous MFC studies (Virdis et al, 2008(Virdis et al, , 2010Xie et al, 2011;Zhang and He, 2012) for combined COD and N removal the three processes where physically separated, thus avoiding the competition between denitrifiers and aerobic heterotrophs for COD; and 3) the high external resistance (1000 U) applied in this study compared to lower external resistances (5 &10 U) used in other studies (Virdis et al, 2008(Virdis et al, , 2010Xie et al, 2011). As described previously, lowering the external resistance will result in more electrons flowing to the cathode, thus increasing bio-electrochemical nitrate reduction (Zhang and He, 2012). Therefore, lowering the external resistance in the RBCeMFC unit could improve N removal at low COD/N ratio by increasing the CE of organic oxidation and thus reducing the COD requirement for denitrification.…”
Section: N Removalcontrasting
confidence: 62%
See 2 more Smart Citations
“…The low TN removal efficiency observed in this study could be due to several factors: 1) the rotation of the cathode discs which exposes the biofilm to oxygen, thus increasing COD losses due to aerobic oxidation; 2) in this study, oxidation of organic matter, nitrification and denitrification occurred in the same reactor, thus increasing competition between denitrifiers and aerobic heterotrophs for COD; whereas in previous MFC studies (Virdis et al, 2008(Virdis et al, , 2010Xie et al, 2011;Zhang and He, 2012) for combined COD and N removal the three processes where physically separated, thus avoiding the competition between denitrifiers and aerobic heterotrophs for COD; and 3) the high external resistance (1000 U) applied in this study compared to lower external resistances (5 &10 U) used in other studies (Virdis et al, 2008(Virdis et al, , 2010Xie et al, 2011). As described previously, lowering the external resistance will result in more electrons flowing to the cathode, thus increasing bio-electrochemical nitrate reduction (Zhang and He, 2012). Therefore, lowering the external resistance in the RBCeMFC unit could improve N removal at low COD/N ratio by increasing the CE of organic oxidation and thus reducing the COD requirement for denitrification.…”
Section: N Removalcontrasting
confidence: 62%
“…Thus, further improvement in TN removal by the RBCeMFC unit could be achieved by lowering the external resistance (i.e. higher electron flow) which would increase bio-electrochemical nitrate reduction (Zhang and He, 2012). In another study, Virdis et al (2010) reported 77.7% removal of N using a two-chambered MFC operated at a COD/ N ratio of 3.02 gCOD g À1 N, HRT of 6.86 h and a resistance of 5 U.…”
Section: N Removalmentioning
confidence: 97%
See 1 more Smart Citation
“…MFCs are capable of efficiently removing a large variety of contaminants from wastewaters, such as nutrients (Min et al, 2005b), recalcitrant cellulose (Aulenta et al, 2011;Kalathil et al, 2011), dyes Mu et al, 2009), leachates (You et al, 2006a), volatile fatty acids (Freguia et al, 2010), metals Zhang B. et al, 2009a) and nitrate and sulfur compounds Zhao et al, 2009;Yan et al, 2012;Zhang and He, 2012). A good effluent quality with COD<20 mg/L can be achieved by MFCs with an optimized reactor configuration and operating condition (Yu et al, 2012).…”
Section: Mfcs For Sustainable Wastewater Treatment: Opportunities Andmentioning
confidence: 99%
“…MFCs are bioelectrochemical reactors in which bacteria oxidize various organic or inorganic compounds in the anode and produce protons and electrons that transport to the cathode to reduce oxygen to water [3]. Electron flow from the anode to the cathode generates an electric current or power if a load is connected.…”
Section: Introductionmentioning
confidence: 99%